Retroauricular dermoid cyst associated with Gorlin syndrome. A case report - A.A. Henares Chavarino; C.P. Bérniz Laborda; M. Estiragués Cerdá; A. Ros Magallón; M. Vicente Ruiz; A. Bazán Álvarez (Elsevier, 2022)
Background: Gorlin syndrome is an autosomal dominant genodermatosis characterized by the early appearance of multiple basal cell carcinomas, odontogenic keratocysts and skeletal abnormalities. It is caused by mutations in the hedgehog signalling pathway, primarily in the tumour suppressor gene PTCH1 (9q22.1-q31). Case summary: We present a 14-year-old girl who consulted for asymmetrical ears, in the context of multiple disorders such as mental retardation, snoring, non-specific coagulation abnormalities, retrognathia, pectus excavatum and scaphoid duplication. During the intervention, a retroauricular cystic tumour was found incidentally, reported by Pathology as a dermoid cyst. The syndrome is confirmed by a genetic study with the result of a new pathological variant in PTCH1. Conclusion: We describe the coexistence of this entity with a dermoid cyst. Furthermore, it is exceptional in its retroauricular location and the pathological point mutation in the PTCH1 gene, consisting of the pCys56Gly variant.